Small Vessel Disease on Neuroimaging in a 75-Year-Old Cohort (PIVUS): Comparison With Cognitive and Executive Tests - Nylander, Ruta; Kilander, Lena; Ahlström, Håkan; Lind, Lars; Larsson, Elna-Marie (Frontiers in Aging Neuroscience, 2018)
Background and Purpose: Signs of small vessel disease (SVD) are commonly seen on magnetic resonance imaging (MRI) of the brain in cognitively healthy elderly individuals, and the clinical relevance of these are often unclear. We have previously described three different MRI manifestations of SVD as well as cerebral perfusion in a longitudinal study of non-demented 75-year-old subjects. The purpose of the present study was to evaluated the relationship of these findings to cognition and executive function at age 75 and changes after five years. Methods: In all, 406 subjects from the Prospective Investigation of the Vasculature in Uppsala Seniors (PIVUS) study were examined with MRI of the brain at age 75 years. Two hundred fifty of the subjects were re-examined 5 years later. White matter hyperintensities (WMHs) and lacunar infarcts (LIs) were assessed on both occasions, but microbleeds (MBs) and perfusion only at age 75. Cognitive function was screened by the Mini Mental State Examination (MMSE). Trail Making Test A and B (TMT-A and TMT-B) were performed at baseline and at follow-up at age 80. Results: At baseline, 93% performed >27 points in the MMSE. The TMT-B at age 75 was significantly related to WMH visual scoring after adjustment for sex, education and cerebrovascular disease risk factors (+80 s (95% CI 0.3-161 s), P<0.05 for grade 2-3 vs grade 0). Neither MMSE nor TMT-A was significantly related to WMH scoring. There was no relation between any test performance and WMH volume, white matter volume, number of MBs or brain perfusion at age 75. Subjects who had sustained a new LI (n=26) showed a greater increase of the time to perform TMT-A at the 5-year follow-up (+25s vs +4s in LI-free subjects, P=0.003). Changes in MMSE or TMT-A and -B test performance between ages 75 and 80 were not related to changes in WMH scoring or volume during the 5 years’ follow-up, or to brain perfusion at age 75. Conclusion: In this cognitively healthy community-based population, moderate-severe WMHs and incident LIs on brain MRI in individuals aged 75-80 years were associated with a mild impairment of processing speed and executive function.